La guerra i la paraula. Sobre els semons patriòtics en valencià durant la guerra de la independència - Casanova, Emili; Martínez, Francesc A. (Caplletra. Revista Internacional de Filologia, 2001)
The edition of two sermons in Valencian by Father Ramon Valcedo, given in Alcoi and Cocentaina to encourage the inhabitants to rise up against the Napoleonic invasion, highlights the use of the autochthonous language by the ecclesiastic hierarchy to get closer to the common people as late as the beginning of the XIX century in the territory of Valencia.